Hypertension as a death risk factor in men and women aged 20-59 years: a 34-year cohort prospective study - I. V. Dolgalev; A. Yu. Ivanova; A. Yu. Shipkhineeva (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To study the effect of hypertension (HTN) on the risk of cardiovascular and all-cause death among men and women aged 20-59 years among Tomsk population in a 34-year cohort prospective study.Material and methods. The study was carried out on the model of Tomsk population. At stage I (1988-1991), 1546 people (630 men and 916 women) aged 20-59 years were examined, the prevalence of hypertension among which was studied. At stage II (2022), the effect of HTN on and all-cause death risk was analyzed.Results. A significant effect of HTN on mortality was revealed: the relative risk (RR) of all-cause and cardiovascular death was 1,9 (p<0,001) and 2,7 (p<0,001), respectively. Among men, HTN increased the risk of all-cause death by 1,4 times (p<0,001); among women — 2,5 times (p<0,001). The RR of cardiovascular death among men with HTN was 1,5 (p<0,05); among women with hypertension — 5,2 (p<0,001). The RR of non-cardiovascular death in HTN persons was 1,4 (p<0,01). Mean blood pressure at primary screening were higher in non-survivors compared to survivors. This pattern was observed in all sex and age groups. Among persons with initially normal blood pressure, the 34-year survival rate was 70,9%, while with increased blood pressure — 45,1%.Conclusion. The results of a 34-year cohort prospective study confirm the significant impact of HTN on the death risk and survival prognosis.